Peran Website Desa dalam Peningkatan Partisipasi Masyarakat Desa Nglanggeran dan Desa Girijati Kabupaten Gunungkidul - Ganda Sibarani (Diponegoro University, 2021)
This study aims to describe the relationship between website exposure variables and community participation variables in village development through the use of village information system communication technology (SIDA) through the provision of village websites so that various data and information related to village policies are quickly and routinely disseminated and easily accessible to residents. Through village websites in Nglanggeran and Girijati Village, Gunungkidul Regency. The research method used is the mix method sequential explanatory design with the method of distributing questionnaires, followed by in-depth interviews and observations. The data obtained were analyzed by non-parametric statistical quantitative analysis. The results of the statistical analysis are then taken to the field to be used as a basis for interviews and qualitative analysis to build theories or patterns of certain knowledge based on participatory perspectives. The findings are in the form of a description of the case and the alleged factors stated in the summary of findings and research on knowledge. The results showed that the existence of the website at the level of government administration was quite effective. However, in increasing community participation, the village website has not been able to create a cognitive, affective and conative impression on increasing awareness in development and community participation. This is due to several factors such as news of the value, consistency and variety of the SIDA program, internet connectivity and ownership of access devices, social capital, oral culture, and policies that are misleading to local governments. To maximize the existence of the website, the community needs to be given strengthening citizen journalism so that the community's active role is in the process of reporting, reporting, analyzing, and presenting better news and promoting communication between citizens and the village government.